TRANSFORMATIONAL LEADERSHIP AS A CATALYST FOR ENHANCING ORGANIZATIONAL CLIMATE IN HIGHER EDUCATION - Suryanadi, Juni; Burmansah, Burmansah; Ardianto , Hendri (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
A positive organizational climate is one of the essential elements in creating a productive, collaborative, and innovative work environment, especially in higher education institutions. However, many higher education institutions face challenges in maintaining a conducive organizational climate due to internal and external dynamics, such as policy changes, work pressure, and the complexity of relationships between individuals. This study explores how transformational leadership improves a positive organizational climate in higher education environments. This study uses a quantitative approach with a survey method involving lecturers and staff from several universities as respondents. Respondents were selected using the purposive sampling method based on specific criteria, with a sample size of 154 out of 250 total population. The study results show that transformational leadership significantly influences a positive organizational climate, including creating a collaborative work atmosphere, increasing work motivation, and encouraging innovation and adaptability. Data analysis indicates that the dimensions of charisma and intellectual stimulation contribute the most to the organizational climate. At the same time, individual considerations play a role in strengthening interpersonal relationships within the team.